Preliminary analysis of the clinical feasibility of a practice intervention derived from the occupational therapy intervention process model for patients with stroke in the convalescence stage. (March 2023) - Choji, Yuki; Kobayashi, Ryuji
Introduction: This study lays the groundwork for the Occupational Therapy Intervention Process Model (OTIPM) run by occupational therapy practitioners for patients with stroke. We explored the feasibility of a treatment approach based on the OTIPM for patients with stroke and the clinical feasibility of evaluating the degree of a collaborative relationship between patients and occupational therapists. Method: This pilot trial was conducted as a one-group pre-test–post-test study and two-group comparison on 16 patients with stroke in the convalescence stage. We used the Canadian Occupational Performance Measure (COPM), Assessment of Motor and Process Skills (AMPS), Functional Independence Measure, Japan Stroke Scale of Motor Function, and the Collaborative Relationship Scale between clients and occupational therapists to assess outcomes. Results: Patients demonstrated a significant improvement on the outcome measures after intervention. Moreover, the good collaborative relationship group demonstrated significantly higher process skills in AMPS and satisfaction in COPM than the poor collaborative relationship group. Conclusion: This preliminary study revealed that short-term OTIPM for patients with stroke may be a feasible clinical practice. In addition, evaluating the degree of the difference in the collaborative relationship between patients and occupational therapists would be a feasible clinical practice.